Reducing Moral Value in Online Learning System; Literature Review - Ruri Supatmi; Malyn Malazarte (LET: Linguistics, Literature and English Teaching Journal, 2023)
Concepts of self, community, and "what is right and wrong" are continually evolving in our education, but online learning system changed all the concept.  This makes it particularly difficult for young people to develop a sense of who they are and to pinpoint their most important values but now the students felt freer when online meeting applications included restrictions. Because of this, they behaved improperly and rudely in front of professors and in online classrooms. The flexibility of online learning changed that since in traditional face-to-face classroom settings, students are under more ethical strain and consequently hesitate before engaging in inappropriate behaviours. What are the behavioural implications of online learning on students? is the issue. Authors seek to ascertain the link between online education and students' conduct, particularly morality and ethics. So, in an effort to lessen the impact and even prevent unforeseen events in the future, consider a potential remedy. Data were collected by the authors using a literature review and a survey, and were then analysed using descriptive and qualitative research. many data collected and described detailed by the researcher. The result is Students' moral values reduced in the process of online learning